2014
DOI: 10.1103/physrevlett.112.218301
|View full text |Cite
|
Sign up to set email alerts
|

Orientationally Glassy Crystals of Janus Spheres

Abstract: Colloidal Janus spheres in water (one hemisphere attractive and the other repulsive) assemble into two-dimensional hexagonal crystals with orientational order controlled by anisotropic interactions. We exploit the decoupled translational and rotational order to quantify the orientational dynamics. Via imaging experiments and Monte Carlo simulations we demonstrate that the correlations in the orientation of individual Janus spheres exhibit glass-like dynamics that can be controlled via the ionic strength. Thus,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“…Most natural expectation would be that the relaxation of the system proceeds as a coarsening process [23] of the stripes. However an experimental study [17] has suggested some sort of glassy dynamics. A stripe is a train of tetramers with the same orientation σ.…”
Section: Out-of Equilibrium Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most natural expectation would be that the relaxation of the system proceeds as a coarsening process [23] of the stripes. However an experimental study [17] has suggested some sort of glassy dynamics. A stripe is a train of tetramers with the same orientation σ.…”
Section: Out-of Equilibrium Monte Carlo Simulationsmentioning
confidence: 99%
“…However the nature of the orientational ordering have not been fully studied yet. While a theoretical study [18] predicts an orientationally ordered state for large enough patch sizes, an experiment [17] suggests an orientational glass phase. In the present work, we perform extensive Monte Carlo simulation to study both the static and dynamic aspects of the orientational configurations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…12 These examples raise interesting puzzles that go beyond simply observing the chirality of the trajectories, puzzles about the relationship between shape and motion, especially when the mounting interest in active material design must ultimately be grounded in coordinating the motion of body parts and the whole body. Regarding the experimental system, this study goes beyond this laboratory's traditional interest in single-component Janus particles [13][14][15] and considers instead the new dynamic structures which result when one mixes Janus particles with isotropic particles, both of them in an electric field. Building upon a preliminary study presented elsewhere 16 in which the Janus particles are repulsive to each other, here we consider particles that mutually attract to form active filaments.…”
mentioning
confidence: 99%
“…However, for colloidal spheres, their rotational dynamics have hardly been explored with confocal microscopy yet. Rotational diffusion of colloidal spheres has been used to explore the decoupling of translational-rotational motion in concentrated colloidal systems [25,26] . In this communication, we demonstrate a quantitative method to concurrently measure the translational and rotational diffusion of colloidal spheres with confocal microscopy.…”
mentioning
confidence: 99%